“Programa Materno – Psicoprofilaxis, enfermedad respiratoria aguda (IRIA), Enfermedad diarreica aguda (EDA)” - Siccha Paima, Melchora del Carmen (1996)
Being the de·finicion of health el· complete well-being f. i.Sico, social and mental person and not merely the absence of disease. Programs give health try to encourage and promote focusing them from several different & attentions, angles, such as = care, preventive, recuperative, educational and promotional; Thus. go to the groups ~ as vulnerabh ~ s. Contemporary medicine is more proactive than recuperafivo approach, ·this desire health programs develop an important role. In the Ministry of health develop ·14 programs: Control of expanded program of immunization (EPI), growth and Oesarrol it (I THINK), ·salud of Es ~ solar and adolescent (BE), Pl ~ nific:acion family (PF), perinatal maternal, oral health, ·. Eye health, health ambien ~ a, Metaxenic diseases, Control of acute diarrhoeal disease (EDA), Control of infection respiratory acute (IRA), Control of sexually transmitted disease and AIDS (STDS), Mental health, Control of...